Left behind: the state of universal health coverage in Europe. (30th September 2020) - Burns, R; Graversen, P; Miller, A; Bader, C; Offe, J; Fille, F; Aldridge, R W
Abstract: Background: Barriers to access healthcare and lack of data undermine Universal Health Coverage (UHC) in Europe, despite the region's clear commitment to the Sustainable Development Goals and UHC. Current indicators measuring unmet healthcare needs in the European Union (EU) often exclude more marginalised groups, further rendering their health needs invisible and the data to inform policy flawed. For effective evaluation of UHC, comprehensive data on the health of these groups is needed. Methods: We conducted an evaluation of humanitarian healthcare provision of people attending Médecins du Monde (MdM) programmes in seven countries in Europe (Belgium, France, Germany, Luxembourg, Sweden, Switzerland, and the United Kingdom). MdM is a humanitarian organisation, providing care to those excluded from mainstream healthcare services. We describe the characteristics of MdM service users, their determinants of health and healthcare access. Results: A total of 29, 359 people were seen between January 2017 and December 2018. Nearly all were migrants (97.2%, 21, 591/22, 136), with 66.3% (11, 690/17, 629) of people reported not having a right or permission to reside in the country they presented in. A majority were living below the poverty line (92.6%, 7, 660/8, 268), residing in insecure housing (44.3%, 8, 895/20, 097) or living as street homeless or in emergency shelters (20.4%, 4, 107/20, 097). Most people reported having no healthcare coverage (81.7%, 14, 848/18, 164). When asked about barriers to accessing healthcare, 20.8% of responses reported economic barriers (3, 960/19, 020) and 14.3% reported a lack of knowledge of health system/entitlements (2, 718/19, 020). Conclusions: This humanitarian service evaluation highlights the intersecting vulnerabilities and barriers to access healthcare for people excluded from mainstream healthcare systems across Europe. Our findings provide a unique insight into the extent of unmet healthcare needs of migrants and other marginalised populations. Key messages: UHC requires comprehensive data on the population groups who are many times left without access to health services and who are often excluded from national data collection and research. A majority of MdM service users do not have healthcare coverage and experience multiple and intersecting barriers to access healthcare across Europe.